TI_GERICHTE 72.2009.153 vom 3. März 2010 , Importazione in Svizzera di 9,480 kg di eroina da parte di due cittadini stranieri - TI Tribunale d'appello (2010)
Importazione in Svizzera di 9,480 kg di eroina da parte di due cittadini stranieri